2013
DOI: 10.1093/infdis/jit425
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Polymerase Gene Polymorphisms Are Associated With Phenotypic Differences in Replication Capacity and Disease Progression

Abstract: HIV-1 pol gene intersubtype and RC differences are associated with disease progression and may be influenced by amino acid polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…However, there are conflicting reports of the disease progression rate of subtype C relative to that of subtypes A and D (12,(15)(16)(17)59). Nevertheless, overall, our data suggest that the lower Gag-protease-driven replication capacity of subtypes A and C (in addition to the lower Pol-driven replication capacity for subtype A [35]) may contribute to slower disease progression in individuals infected with these subtypes. The associated increased longevity is expected to result in greater opportunity for transmission (17) and hence in an increased prevalence of these subtypes.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, there are conflicting reports of the disease progression rate of subtype C relative to that of subtypes A and D (12,(15)(16)(17)59). Nevertheless, overall, our data suggest that the lower Gag-protease-driven replication capacity of subtypes A and C (in addition to the lower Pol-driven replication capacity for subtype A [35]) may contribute to slower disease progression in individuals infected with these subtypes. The associated increased longevity is expected to result in greater opportunity for transmission (17) and hence in an increased prevalence of these subtypes.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, biological differences between subtype C and subtype B and/or other subtypes in the Env (29), reverse transcriptase (30), protease (31), Vif (32), and long terminal repeat (LTR) regions (33,34) have been reported; however, the implications of these factors for disease progression and epidemic spread remain unclear. More recently, a study of Ͼ100 clinical isolates showed that subtype D had higher Pol-driven replication capacity than subtype A and directly linked these differences to faster disease progression in the former than in the latter subtype (35). Furthermore, we recently demonstrated subtype-specific differ-ences in Nef function (36) and showed that Nef functional differences in acute infection correlate with markers of disease progression (37).…”
mentioning
confidence: 95%
“…While our study focusses on the subtype based differences in the Env glycoprotein, the role of other viral proteins like Pol and Gag in this phenomenon cannot be overlooked. Ng et al described that polymorphisms in the pol gene were responsible for differences in replication capacity and disease progression in subtype A and D HIV infected individuals in Uganda (Ng et al, 2014). Similarly, Clairborne et al attributed the early T-cell activation and immune dysfunction in HIV infected Zambians to the replicative fitness of the transmitted virus with the gag gene contributing significantly to the phenomenon (Claiborne et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified a valine instead of an isoleucine at position 62 and 64 in the protease (I62V and I64V), and a proline instead of an alanine at position 272 in the reverse transcriptase as amino acid substitutions that could be associated with perparasite pathogenicity (Ng et al, 2014) (see the Result section for more details). To test for associations of per-parasite pathogenicity with the substitutions I62V, I64V, and A272P, we regressed per-parasite pathogenicty, but also the other two traits, set-point viral load and CD4+ T cells decline, against categorical variables indicating the presence of the mutated amino acid at the respective position.…”
Section: Testing For Genetic Associations With Per-parasite Pathogenimentioning
confidence: 99%
“…These intersubtype difference in disease progression have been mapped to the pol gene and were associated with replicative capacity (Ng et al, 2014). In particular, a valine instead of an isoleucine at position 62 and 64 in the protease (I62V and I64V), and a proline instead of an alanine at position 272 in the reverse transcriptase were found to be associated with high replicative capacity (Ng et al, 2014) We tested if these amino acid polymorphisms are associated with set-point viral load, CD4+ T cell decline, and per-parasite pathogenicity within HIV-1 subtype B. Indeed isoleucine and valine at positions 62 and 64 of the protease, and alanine and proline at position 272 in the reverse transcriptase were the most prevalent amino acids in our study population.…”
Section: Testing For Genetic Associations With Per-parasite Pathogenimentioning
confidence: 99%